Towards a Future of Equal Opportunity: Mentoring and Support Networks for Women's Empowerment in Organizations - Chuco Aguilar, Victoria Judith (2023)
The "glass ceiling", or the persistent underrepresentation of women in leadership and decision-making positions in the workplace, is a problem that persists despite the progress made towards gender equality. In this sense, this article aims to conduct a comprehensive review of the existing literature on mentoring and support networks in the career advancement of women in the workplace. According to the findings, mentoring can help women advance in their careers by providing them with learning opportunities, emotional support and guidance. It is concluded that, in order to advance towards gender equality in the workplace, it is crucial to implement policies that take into account women's family responsibilities, through measures that can be adapted to particular social and cultural contexts.